Implementasi Kombinasi 3IC Tools Sebagai Penentu Optimasi Pengendalian Persediaan Minyak Goreng - Hery Purnomo; Lilia Pasca Riani (Jurnal Ekonomi, 2018)
The purpose of this study was: 1) To analyze the brands of cooking oil that entered the class A classification using the ABC method, 2). To maximize safety stock that must be provided, and 3) determine the most Reorder Point for cooking oil products that enter in class A. This research is a descriptive research with quantitative approach. Data collection uses observation, and interview studies. In data analysis techniques, the authors do it in three stages, namely the first stage of ABC analysis to identify products in class A, B, or C; the second stage calculates safety stock for cooking oil products that enter class A; and the third stage determines the size of the Reorder Point. Then taken the conclusion according to the purpose of research. The results of this research show that from 86 types of brands and packaging of cooking oil, there are 28 packs that belong to category A, with the highest safety stock calculation is on Sugarap brand oil of Reffil 2 Liter, and Reorder Point at most on brand oil of Rosebrand Packaging Reffil 1 liter.